PELAKSANAAN KEDISIPLINAN SISWA MELALUI SISTEM POIN DI SMA NEGERI 2 KEC. BUKIK BARISAN - Wiken Purnama Sari; Darul Ilmi; Iswantir M; Jasmienti Jasmienti (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
The purpose of this study was to determine the implementation of student discipline through a point system, to find out the obstacles faced in the implementation of discipline through a point system to improve student discipline at SMA Negeri 2 Kec. Bukik Barisan. This research uses the type of field research (field research). The form of research used by the author is descriptive research with qualitative descriptive methods. Informants in this study were divided into two, namely key informants (PAI teachers at SMA Negeri 2 Bukik Barisan district) and supporting informants (student assistants, Counseling Guidance teachers, and students at SMA Negeri 2 Bukik Barisan district). Data collection techniques in this study using observation and interviews. The results of the study concluded that the implementation of student discipline through the point system since it was established has been going quite well with the support of many parties, such as all school members, principals, teachers, parents, and most of the students. The existence of this point system will make it easier for teachers to give sanctions to students who violate the rules, make students deterrent from committing violations because every student who violates gets a point weight, students become more disciplined. The obstacles faced by schools, such as obstacles from students themselves who have basic characters that are difficult to manage, lack of support and attention from parents for their children's development, and are constrained by administration that has not been perfectly organized